Childhood sacrococcygeal teratoma: a clinicopathological study - Kamal Nain Rattan; Hemant Yadav; Divya Srivastava; Ananta Rattan (Hygeia Press di Corridori Marinella, 2018)
Background: Sacrococcygeal teratoma (SCT) is a relatively uncommon tumor affecting neonates, infants, and children with a female preponderance. Age is an important predictor of malignancy in SCT. Early antenatal diagnosis influences the management and provides a better outcome. Aim: The present study was carried out to describe in detail various clinicopathological features and outcome of SCT patients; as many reports are available from the West, there is a paucity of literature on this entity from the Eastern region, especially India, which has a unique socioeconomic and demographic background. Materials and methods: The study included 52 patients of SCT operated for 16 years from 2000 to 2015. A retrospective review of various parameters was done from the medical case records available in the Department of Pediatric Surgery (PGIMS, Rohtak, Haryana, India). Result: There were 40 females and 12 males with age ranging from newborn to 13 years. Thirty-three children (63%) presented in the neonatal age group. There were 40 cases of benign (mature), 7 immature and 5 malignant teratomas. Four cases had a recurrence on follow-up. Out of 52 patients, 7 died while the others are doing well on follow-up. Conclusion: A prenatal diagnosis of SCT is essential for reducing morbidity and mortality. Delayed presentation and the presence of malignant changes continue to be poor prognostic factors. Strict follow-up by clinical examination, ultrasound and tumor markers is mandatory to look for any recurrence.